2001
DOI: 10.1177/1362361301005004006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Outcome in Young Children with Autism

Abstract: This study examined predictors of developmental outcomes in 17 children diagnosed with autism or PDD-NOS, who received generic treatment over a mean period of 37 months. Pre-treatment evaluations occurred at a mean age of 31 months with follow-up evaluations at a mean age of 69 months. Significantly different developmental trajectories were observed among the participants at follow-up, separating the participants into two distinct groups (high and low outcome). However, groups did not differ significantly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 26 publications
6
73
0
Order By: Relevance
“…Although this paper did not explicitly discuss optimal outcome or loss of diagnosis, the smaller, high-functioning group showed mean verbal and nonverbal scores within the normal range, and few autism symptoms; many of them would probably have met our current definition for recovery. Gabriels et al (2001) also found two clearly separable developmental trajectories in a group of individuals with ASD who were studied from preschool to school-age. Unlike Stevens et al (2000), however, Gabriels and colleagues found that in both groups, IQ tended to increase across development.…”
Section: Evidence For Recoverymentioning
confidence: 96%
See 3 more Smart Citations
“…Although this paper did not explicitly discuss optimal outcome or loss of diagnosis, the smaller, high-functioning group showed mean verbal and nonverbal scores within the normal range, and few autism symptoms; many of them would probably have met our current definition for recovery. Gabriels et al (2001) also found two clearly separable developmental trajectories in a group of individuals with ASD who were studied from preschool to school-age. Unlike Stevens et al (2000), however, Gabriels and colleagues found that in both groups, IQ tended to increase across development.…”
Section: Evidence For Recoverymentioning
confidence: 96%
“…In addition to the confounding factor that Gabriels et al (2001) suggested, another potential confound could work in the opposite direction: children who make slower progress are sometimes given more intensive treatment, making interpretation of the relationship between progress and treatment intensity very difficult. All of the children in the studies that reported participants with optimal outcome were receiving at least some level of treatment and thus it is possible that the treatment, in combination with the potential for normal levels of cognition, was responsible for their improvements.…”
Section: Predictors Of Outcome: Treatment Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that PECS may be more effective for children at the pre-request stage and RPMT may be more effective for children with some ability to initiate joint attention. Other studies have investigated parent and environmental predictors of intervention response (Ben Itzchak & Zachor, 2011;Gabriels, Hill, Pierce, Rogers, & Wehner, 2001;Osborne, McHugh, Saunders, & Reed, 2008;Robbins, Dunlap, & Plienis, 1991). This direction is encouraging as it better takes into account the heterogeneity of ASD and allows for intervention to be tailored to needs and abilities, rather than based on a categorical diagnosis.…”
Section: Individualized Interventionsmentioning
confidence: 99%